2011
DOI: 10.1371/journal.pgen.1002298
|View full text |Cite|
|
Sign up to set email alerts
|

Identification, Replication, and Fine-Mapping of Loci Associated with Adult Height in Individuals of African Ancestry

Abstract: Adult height is a classic polygenic trait of high heritability (h 2 ∼0.8). More than 180 single nucleotide polymorphisms (SNPs), identified mostly in populations of European descent, are associated with height. These variants convey modest effects and explain ∼10% of the variance in height. Discovery efforts in other populations, while limited, have revealed loci for height not previously implicated in individuals of European ancestry. Here, we performed a meta-analysis of genome-wide association (GWA) results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 22 publications
(30 reference statements)
4
92
1
Order By: Relevance
“…HMGA2 has been associated with height determination in multiple human GWAS (Weedon et al 2007(Weedon et al , 2008Gudbjartsson et al 2008;Lettre et al 2008;Sanna et al 2008;Soranzo et al 2009;N'Diaye et al 2011;Carty et al 2012). HMGA2 is a transcription factor expressed during embryonic and fetal development (Rogalla et al 1996;Gattas et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMGA2 has been associated with height determination in multiple human GWAS (Weedon et al 2007(Weedon et al , 2008Gudbjartsson et al 2008;Lettre et al 2008;Sanna et al 2008;Soranzo et al 2009;N'Diaye et al 2011;Carty et al 2012). HMGA2 is a transcription factor expressed during embryonic and fetal development (Rogalla et al 1996;Gattas et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…GWAS in humans have identified 180 loci significantly associated with height (Gudbjartsson et al 2008;Lettre et al 2008;Sanna et al 2008;Weedon et al 2008;Soranzo et al 2009;Kim et al 2010;Lango Allen et al 2010;N'Diaye et al 2011;Carty et al 2012). However, even together, these loci account for only ;10% of the adult human height variation (Lango Allen et al 2010), although the heritability of height is ;80% (Silventoinen 2003;Visscher et al 2006;Perola et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We created a list of 66 regions from this list of 130 SNPs by grouping SNPs located within 50 kb of each other, and then adding 10 kb to each end of each resulting start and end position (e.g., such that an individual SNP not located within 50 kb of another significant SNP would be represented in a region of 20,001 bp centered around the significantly associated SNP; Dataset S4). We also analyzed a set of candidate African stature SNPs reported by N'Diaye et al (39). The authors of this study began with a database of European GWAS height SNPs, but then identified the tag SNPs for each locus that best reflected linkage disequilibrium patterns in Africans.…”
Section: Methodsmentioning
confidence: 99%
“…S6). We also considered our 1M SNP genotype data against stature association results from two previous genomic studies of west central African rainforest huntergatherers (6,29) and with a set of candidate height SNPs for individuals of African descent (39).…”
Section: Batwa-baka Comparison Suggests Pygmy Phenotype Convergencementioning
confidence: 99%
“…Furthermore, the best associated SNP in African‐derived populations was associated with LCORL gene expression levels in lymphoblastoid cell lines derived from 56 unrelated Yoruba individuals ( P = 0.0026) (N'Diaye et al . 2011). In contrast, Lango Allen et al .…”
Section: Ncapg‐lcorlmentioning
confidence: 99%